PENGARUH METODE PEMBELAJARAN PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA MATERI IKATAN KIMIA KELAS X MIPA SMA - Viya Lestari; Rachmat Sahputra; Rahmat Rasmawan; Eny Enawaty; Rody Putra Sartika (Universitas Tanjungpura, 2022)
Chemical bonding is one of the subjects that are considered difficult by students, so it is necessary to have a model or learning method that can improve student learning outcomes on the matter of chemical bonds, so we need a method that can improve student learning outcomes, namely Problem Solving. The purpose of this study was to determine differences in learning outcomes and the effect of using the Problem Solving method on chemical bonding material for class X MIPA SMA Negeri 7 Singkawang Timur. The method used in this research is Quasi Experimental Design with Nonequivalent Control Group Design. The sampling technique carried out by the researcher was saturated sampling totaling 70 people consisting of class X MIPA 1 and X MIPA 2. Data collection tools used learning outcomes tests, observation sheets and interview guidelines. The instrument used is a question of pretest and posttest with a content validity level that has been declared valid and the reliability result is 0.846. Data analysis technique with inferential statistics. The results of the hypothesis using the independent sample t-test test of sig (2-tailed) 0.016 <0.05. In the test results the effect size is , in the high category. Based on the results of the analysis of the data obtained, it is concluded that there are differences in learning outcomes between the experimental class and the control class as well as the effect of using problem solving methods in improving student learning outcomes on chemical bonding material.